Constrained discretion and central bank transparency - Francesco Bianchi; Leonardo Melosi (Federal Reserve Bank of Chicago, 2016)
We develop and estimate a general equilibrium model to quantitatively assess the effects and welfare implications of central bank transparency. Monetary policy can deviate from active inflation stabilization and agents conduct Bayesian learning about the nature of these deviations. Under constrained discretion, only short deviations occur, agents' uncertainty about the macroeconomy remains contained, and welfare is high. However, if a deviation persists, uncertainty accelerates and welfare declines. Announcing the future policy course raises uncertainty in the short run by revealing that active inflation stabilization will be temporarily abandoned. However, this announcement reduces policy uncertainty and anchors inflationary beliefs at the end of the policy. For the U.S., enhancing transparency is found to increase welfare. The same result is found when we relax the assumption of perfectly credible announcements.
Keywords: E52; D83; C11; 330; Policy announcement; Bayesian learning; reputation; forward guidance; macroeconomic risk; uncertainty; inflation expectations; Markov-switching models; likelihood estimation